Hepatitis C virus seroprevalence in Mongolian women assessed by a novel multiplex antibody detection assay - Dondog, Bolormaa; Schnitzler, Paul; Michael, Kristina M.; Clifford, Gary; Franceschi, Silvia; Pawlita, Michael; Waterboer, Tim (Cancer epidemiology, biomarkers & prevention, 2015)
Background: Hepatitis C virus (HCV) infection causes hepatocellular carcinoma and is an important cause of mortality in both industrialized and developing countries. We developed a single-step high-throughput multiplex serology assay for HCV antibody detection and determined HCV prevalence in a highly endemic country. - Methods: Five proteins (Core, NS3, NS4A, NS5A, NS5B) each from the three most common subtypes of HCV (1a, 1b, 2a) were recombinantly expressed and used as antigens in a multiplexed antibody detection assay. Multiplex HCV serology was validated with 432 reference sera whose HCV status was established by commercial ELISA, Western blot, and RNA assays. HCV antibodies were determined in 1,023 sera representative for the adult female population of Mongolia. - Results: In reference sera, detection of HCV (mostly Core and NS3) antibodies by multiplex serology showed 100% sensitivity and 99.6% specificity, and was in very good agreement with the commercial diagnostic assays (kappa, 0.96; 95% confidence interval, 0.92-0.99). The role of antibodies to NS4 and NS5 remains to be evaluated. In Mongolia, overall HCV antibody prevalence was 18.9% (17.8% when age-standardized to the world population). HCV seroprevalence increased with age from 10% in women <30 years to 32% in women ≥50 years, but was not related to sexual risk factors. - Conclusions: The single-step high-throughput multiplex HCV serology assay performs similarly to conventional HCV antibody screening followed by secondary confirmation assays. A very high HCV seroprevalence was confirmed across all socio-economic groups in the female population of Mongolia. - Impact: Multiplex HCV serology facilitates large seroepidemiologic studies of HCV infection. Cancer Epidemiol Biomarkers Prev; 24(9); 1360-5. ©2015 AACR.
Gesehen am 22.06.2020